The Relationship Of Breast Care And Interest In Breastfeeding With The Smoothness Of Breast Milk Production In Breastfeeding Mother At Integrated Health Service Work Area Mopah New Health Center, District Merauke In 2023 - Dinik Martiani; Miftakhur Rohmah; Agusta Dian Ellina; Erma Retnaningtyas (Journal of Health Science Community, 2024)
One of the causes of insufficient breast milk production is the lack of implementation of breast care and the mother's low interest in breastfeeding regularly. This study aims to determine the relationship between breast care and interest in breastfeeding with the smooth production of breast milk (ASI) in breastfeeding mothers at posyandu in the Mopah Baru Community Health Center Working Area, Merauke Regency in 2023. This research uses an analytical observational research design with a cross sectional approach. Using a purposive sampling technique, a sample of 36 respondents was obtained, the independent variable (the relationship between breast care and interest in breastfeeding) and the dependent variable (the smooth production of breast milk (ASI)) using a questionnaire. The Chi-Square statistical test was used to determine the relationship between the two variables. The results of research from 36 respondents showed that the majority of respondents did not perform breast care, namely 24 respondents (66.7%), the majority had a high interest in breastfeeding, namely 23 respondents (63.9%), and the majority of respondents had milk production. There were 21 respondents (58.3%) who were breastfeeding smoothly. Analysis using the Chi-Square statistical test found that there was a relationship between breast care and the smooth production of breast milk (ASI) in breastfeeding mothers at the posyandu in the Mopah Baru Community Health Center Working Area, namely p value = 0.000 < 0.05, and there was a relationship between interest in breastfeeding and the smooth production of water. Mother's milk (ASI) in breastfeeding mothers at the posyandu in the Mopah Baru Community Health Center Working Area is p value = 0.001 < 0.05. Proper breast care and a high interest in breastfeeding are related to the smooth flow of breast milk so that in order to produce breast milk more smoothly, it is necessary to carry out routine breast care and it is necessary to foster a high interest in breastfeeding. Therefore, it is hoped that breastfeeding mothers can routinely apply breast care and can foster a high interest in breastfeeding so that breast milk production runs smoothly.